Analisis Penerimaan Pendapatan Pajak Daerah Di Kabupaten Siau Tagulandang Biaro (SITARO) - Mangeber, Sandy Robert; Lambey, Robert; Tangkuman, Steven J. (Riset Akuntansi dan Portofolio Investasi, 2024)
Regional taxes are an obligation that must be paid by the community as taxpayers to local governments, functioning to finance regional infrastructure development aimed at improving community welfare. This study aims to determine the tax revenue revenue from each type of regional tax in SITARO Regency by showing the achievement of the target and percentage of tax revenue realization in 2018–2022. The method used in this study is qualitative-descriptive with primary and secondary data sources. The data collection techniques are interviews and documentation. The results of the study show that SITARO Regency's regional tax revenue from 2018 to 2022 fluctuated with an achievement rate of 94%. Meanwhile, the percentage realization of each type of regional tax is: hotel tax of 76%; restaurant tax of 109%; entertainment tax revenue only existed in 2019 and 2020 by 100%; billboard tax of 99%; street lighting tax of 92%; groundwater tax of 30.82%; tax on non-metallic minerals and rocks at 96.94%; PBB P2 by 92.58%; and BPHTB by 115.49%. From the total, it can be concluded that the increase and decrease in tax revenue are due to a lack of public understanding and awareness of paying taxes. The Regional Revenue Division of SITARO Regency sets the tax target budget to not be too high so that the realization can be maximized.